Hip Dislocation in a Calf - Treatment with Iliofemoral Suture - Silva, Paloma Coutinho [UNESP]; Aoyama, Igor Hideo Andrade; Teodoro, Ananda Neves [UNESP]; Sartori, Vitor Cibiac; Espinoza, Marcio de Freitas; Picelli, Julia Perinotto; Bertonha, Candice Mara; Alves, Endrigo Gabellini Leonel (Univ Fed Rio Grande Do Sul, 2022)
Background: Coxofemoral dislocation is uncommon in large animals, due to anatomical particularities that provide greater stability to this joint. The most common causes of hip dislocation in large animals are related to hypocalcemia, mount trauma, sudden falls on hard surfaces or dystocia. Treatment can be performed by closed reduction, but the reported results are not satisfactory with complications. Several surgical techniques have already been described and successfully used in small animals in the treatment of hip dislocation. The present work aims to describe the technique and the result of the iliofemoral suture in the treatment of hip dislocation in a Girolando heifer. Case: A heifer was attended with a history of difficulty in getting up. According to the owner, the clinical manifestation was sudden, after remaining in a paddock with other animals of different age groups. The calf had reduced skin sensitivity on the croup, and it was impossible to remain in the quadrupedal position, often remaining in sternal recumbency with the left pelvic limb in extension. From the clinical examination, spinal cord injury was suspected and clinical treatment was instituted with dexamethasone, vitamins B1, B12 and dimethylsulfoxide. At the end of the clinical treatment, the animal did not show a favorable evolution, so radiographic examination of the coxofemoral region was performed, revealing dislocation of the left femoral head, indicating surgical correction. Xylazine was administered as pre-anesthetic medication, followed by anesthetic induction with midazolam associated with ketamine, followed by orotracheal intubation. Anesthetic maintenance was instituted with isoflurane and monitoring was performed with a multiparameter monitor. An epidural block was performed with bupivacaine and morphine. A craniolateral approach to the left hip joint was performed. After the dislocation was reduced, sutures were used to better stabilize the joint in question. Following the evolution of the surgical procedure, it was possible to confirm that the femoral head remained in place. After 15 days, the skin stitches were removed and the animal was discharged from the hospital and returned to its original property. The calf was asked to remain in the stall for at least 60 days, gradually releasing it into larger spaces and only after 120 days could it remain in the paddock with other animals. During three months, the tutor was consulted about the evolution of the condition, reporting that the animal was clinically well, being able to get up and walk without difficulty and with a mild degree of lameness, thus suggesting the success of the surgical procedure. Discussion: There are few studies of successful surgical treatments of hip dislocation in large animals, and that number is even smaller when considering cattle alone. It is believed that this is due to difficulties related to the surgical technique and to postoperative handling, given the animal's weight. The iliofemoral suture technique performed on the animal in the present study is commonly employed in small animals, and excellent results have been observed. However, reports on the use of this technique in large animals have not been found. The iliofemoral suture technique has advantages over other reported surgical techniques in cattle. When compared to the femoral head and neck resection, the iliofemoral suture has several advantages, as it allows preservation of the joint and achievement of superior biomechanical results. When compared to the technique of reinforcement of the joint capsule with synthetic material, also reported in cattle, the iliofemoral suture appears to be faster, simpler and more economic, and provides similar stability. We conclude that the iliofemoral suture proved to be a satisfactory alternative for the treatment of hip dislocations in young cattle.
Keywords: Claudication; Joint stabilization; Ruminants; Articulation; Orthopedics